Preparation and In Vitro Characterization of Triamcinolone Acetonide-Loaded Lipid Liquid Crystal Nanocarriers for Ocular Delivery - Fatemeh Asgharian Rezae; Malihe Karimi; Hossein Kamali; Bizhan Malaekeh-Nikouei (Advanced Pharmaceutical Bulletin)
Purpose: This study aimed to develop sustained-release triamcinolone acetonide (TA) formulations using lipid liquid crystals (LLCs) for ocular drug delivery and to characterize the designed formulations. Methods: Eighteen dispersed LLC formulations were prepared through a top-down approach, incorporating varying concentrations of TA and different proportions of glyceryl monooleate, deionized water, and pluronic F127. An additional formulation comprising TA: hydroxypropyl beta-cyclodextrin (HPβCD) complex was also developed to investigate the influence of HPβCD on the properties of the formulations. The formulations were evaluated for their rheological properties in room temperature using a rheometer, syringeability by passing them through a 27G needle, size measurements via dynamic light scattering (DLS), and morphology through polarized light microscopy (PLM). Furthermore, the prepared formulations were injected into a dialysis tube and placed in a phosphate buffer at pH 7.4 and 37 °C for in vitro release evaluation. Samples were taken at predetermined intervals and stored in a refrigerator until HPLC analysis. The percentage of Encapsulation efficacy and drug loading were evaluated using an indirect method. A reversed-phase HPLC method was employed to quantify the drug concentrations in the samples. Results: All selected formulations demonstrated acceptable parameters, including particle size (less than 200 nm), polydispersity index (PDI) ranging from 0.202 to 0.355, and zeta potential values between -14.3 and -32.8 mV. Additionally, the formulations showed good syringeability and achieved 100% drug release within 48 hours (except for the formulation containing HPβCD). PLM analysis revealed the presence of hexosomes and cubosomes, indicating that an increase in hexosomes contributed to a more uniform drug release from the formulations. Conclusion: Overall, the study findings suggest that liquid crystalline carriers can be a promising formulation for sustained ocular drug delivery of TA.